Photosynthetic efficiency and acid tolerance in Pumiliosphaera acidicola KMJ isolated from a geothermal spring in West Java, Indonesia - Kono, Alfredo; Pertiwi, Berliana Gita N.; Farhan, Bahzad Ahmad; Rahmawan, Anhar; Rachmayanti, Yanti; Putri, Rindia M.; Nurachman, Zeily (Acta Biochimica Indonesiana, 2025)
Background: Acidophilic microalgae represent a promising yet underexplored resource for biotechnological carbon capture in low-pH environments such as geothermal springs and industrial effluents. However, few strains have been physiologically characterized, and most biotechnologically relevant microalgae remain neutrophilic. Objective: This study aimed to isolate and characterize an acid-tolerant green microalga from a geothermal spring in Kamojang, West Java, Indonesia, and assess its growth, acid tolerance, and photosynthetic performance across a range of inorganic carbon (Ci: CO₂, HCO₃⁻, and CO₃²⁻) concentrations. Methods: Mud samples were enriched in Allen medium under continuous illumination. Isolates were identified via 18S rRNA sequencing and phylogenetic analysis. Growth was tested across pH 2.3 to 7.0 in media acidified with either HCl or H₂SO₄. Photosynthetic performance was evaluated by O₂ evolution under various Ci concentrations. Results: The isolated strain, designated Pumiliosphaera acidicola KMJ, exhibited robust growth from pH 2.3 to 7.0 and showed comparable tolerance to both HCl and H₂SO₄. Morphologically, KMJ displayed compact, spherical green cells (2–5 µm diameter). Oxygen evolution measurements revealed consistently higher photosynthetic rates than Chlamydomonas reinhardtii, particularly under sub-saturating Ci levels, indicating efficient CO₂ assimilation under acidic, low-Ci conditions. To our knowledge, this is the first study to directly quantify Ci-dependent O₂ evolution in an acidophilic chlorophyte. Conclusion: P. acidicola KMJ combines broad acid tolerance with high photosynthetic efficiency, positioning it as a strong candidate for CO₂ capture in acidic environments. Its physiology also provides a basis for future molecular studies into acidophilic CO₂ assimilation.